The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.3389/fvets.2018.00202
|View full text |Cite
|
Sign up to set email alerts
|

Working Dogs Drinking a Nutrient-Enriched Water Maintain Cooler Body Temperature and Improved Pulse Rate Recovery After Exercise

Abstract: Exercise-related physiological changes were evaluated in hydrated, exercise-conditioned working dogs with free access to tap water (TW) with or without a nutrient-enriched water supplement (NW). Physiological samples and measures were collected before and after work-related field tasks in a warm and moderately humid ambient environment. In a cross-over design study, 12 dogs (age range 8–23 months) were evaluated on 3 separate occasions within each period with exercise bouts up to 30 min, on days −4, 3, and 11.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 47 publications
0
6
1
Order By: Relevance
“…A study based on sport dogs, which measured core body temperature with ingestible sensors and ear temperature with IRT, reported temperature returning to resting levels 60 min after exercise [19]. In our study, however, the surface temperature in all regions was not significantly elevated above pre-exercise levels beyond the cessation of exercise on the treadmill.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…A study based on sport dogs, which measured core body temperature with ingestible sensors and ear temperature with IRT, reported temperature returning to resting levels 60 min after exercise [19]. In our study, however, the surface temperature in all regions was not significantly elevated above pre-exercise levels beyond the cessation of exercise on the treadmill.…”
Section: Discussioncontrasting
confidence: 81%
“…Studies based on a group of baboons indicated that excitement increased the heart rate from 75 ± 4 to 208 ± 14 beats/min and mean arterial pressure from 92 ± 3 to 144 ± 9 mmHg (p < 0.01) [27]. In the literature, it is well documented that any type of positive stress caused by excitement induces an increase in core body temperature, leading to an elevated surface temperature in dogs [13,19]. A study on the emotional state of Beagles concluded that the dogs were excited not only by the expectation of a reward, but also by the realization that they themselves can control access to the reward [26].…”
Section: Discussionmentioning
confidence: 99%
“…Other factors are unknown beforehand (e.g., novel floor surface), may have an inconsistent effect (e.g., wind speed and direction), and may not result in changes in performance apparent to the handler (e.g., helicopter transport) [25]. Whatever form these factors may take, further exploration is needed to identify the specific impact on performance, develop monitoring tools, and devise mitigations to sustain performance wherever possible [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Working dogs have increased nutritional demands due to the nature of their work. Detection and protection dogs often work in adverse environments and are engaged in physical activity that can lead to dehydration (78)(79)(80). Even 15 min of retrieving a ball can lead to fluid loss and detectable dehydration (81).…”
Section: Nutrition Provision Of Food and Hydrationmentioning
confidence: 99%